The Relationship between the Ethical Behavior of the Leadership And the Spirituality of the Work Place: An Empirical Study of the Role of Psychological Empowerment As a Mediator Variable - Abo Lifa, Sanaa (The Arab Journal of Administration, 2019)
The study aims at examining The Relationship between the ethical behavior of the leadership and the spirituality of the work place. A sample of (381) employees working in Telecom Egypt. Questionnaire used to collect the required data. The study revealed a moderate degree of Ethical Behavior of the Leadership, Psychological Empowerment and Spirituality in Workplace. The Psychological Empowerment mediated the relationship between ethical behavior of the leadership and spirituality of the work place. The study concluded with some relevant recommendations.